On the validity of single tests, two-test combinations and the full Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) in detecting patients with cognitive impairment. (December 2020) - Baetge, Sharon Jean; Filser, Melanie; Renner, Alina; Ullrich, Sebastian; Lassek, Christoph; Penner, Iris-Katharina
Background: The international standard to screen for cognitive impairment in multiple sclerosis (MS) is BICAMS (Brief International Cognitive Assessment for MS). However, with an application time of approximately 20 minutes, the battery might be too time consuming from a pragmatic perspective of a routine examination. Objectives: To examine the relative sensitivity and specificity of a BICAMS short version and its validity compared to the total battery. Methods: The German BICAMS version was applied comprising the Symbol Digit Modalities Test (SDMT), the Brief Visuospatial Memory Test–Revised (BVMT-R) and the Rey Auditory Verbal Learning Test (RAVLT; German VLMT). Single tests and two-test combinations were compared regarding conformity with the total battery. Results: Examining 1320 MS patients, the two-test combination of SDMT-BVMT-R was the most sensitive (92.7%) to impairment and showed the strongest agreement with the total battery (κ = 0.95). Performing binary logistic regression analyses, this combination was also validated by its association with employment status. Conclusion: Application of the total BICAMS battery should be the goal to strive for. However, in time-restricted clinical settings, the combined application of SDMT and BVMT-R is a recommendable alternative with an application time of 10 minutes, while single tests alone are not sufficiently sensitive.